1996
DOI: 10.1159/000264273
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Marker Screening in Multifetal Gestations: Failure to Predict Adverse Pregnancy Outcomes

Abstract: The objective of the study was to assess whether the association known in singleton pregnancies of high maternal serum α-fetoprotein (AFP) or human chorionic gonadotropin (HCG) with adverse outcomes applies also to multifetal gestations. Maternal serum AFP and HCG were evaluated in 207 multifetal pregnancies. High values were defined as a maternal serum AFP of > 4.5 and a HCG of > 4.0 multiples of the median (MoM), with appropriate adjustments. Results were correlated with premature delivery, stillbirths, or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Plasma levels are maintained at this lower level for the remainder of pregnancy [11] . There are many reports regarding hCG in twin gestations, and most have found that the concentration of hCG is almost 2 MoM [12,13] . In the present study, the preoperative concentration of hCG in TTTS was 6.34 MoM (interquartile range 3.52-9.86), which is significantly higher than that of normal twin gestations.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels are maintained at this lower level for the remainder of pregnancy [11] . There are many reports regarding hCG in twin gestations, and most have found that the concentration of hCG is almost 2 MoM [12,13] . In the present study, the preoperative concentration of hCG in TTTS was 6.34 MoM (interquartile range 3.52-9.86), which is significantly higher than that of normal twin gestations.…”
Section: Discussionmentioning
confidence: 99%
“…This value converted to 5.39 multiples of the median (MoM) (IQR, 2.83 -8.64 MoM) based on the median hCG value (18,000 mIU/mL=1 MoM) of singleton pregnancies in our institution examined at the same gestational age, significantly higher than in normal twin pregnancies, which have been reported to be almost 2 MoM (Fig. 1-A) [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…In singleton pregnancies, by the beginning of the 2 nd trimester, as hCG secretion declines, serum fT4 and fT3 concentrations decline, and serum TSH concentrations rise slightly (within the normal range). Some reports have demonstrated that compared to singleton gestations, the concentration of hCG in twin gestations is almost 2 MoM [16,17]. Because of higher hCG concentrations in women with multiple pregnancies, hyperthyroidism may be experienced more frequently in these women than in those with normal singleton pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…If laboratory sample size did not permit, then combining whites with Hispanics, and African Americans with Asians would be the next best approach. The same concept has now been expanded to hCG and uE3 with the same conclusions [15,41].…”
Section: Race Adjustmentsmentioning
confidence: 97%